2020
DOI: 10.3389/fimmu.2020.00529
|View full text |Cite
|
Sign up to set email alerts
|

CCR4+ Skin-Tropic Phenotype as a Feature of Central Memory CD8+ T Cells in Healthy Subjects and Psoriasis Patients

Abstract: The chemokine receptor CCR4 has emerged as a skin-homing molecule important for the migration of T cells from the blood to the dermis. From our previous data on psoriasis patients, CCR4 + memory T cells emerged as a putative recirculating population between skin and blood. Here we focused our attention on the expression of CCR4 and skin-tropic molecules in the different stages of memory T cell differentiation. We analyzed the chemokine receptor profile in CD8 + and CD4 + CD45RA − CCR7 + (T CM) and CD45RA − CCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 36 publications
3
19
0
Order By: Relevance
“…Chemokine-induced trafficking and recruitment of leukocytes is involved in the inflammatory response ( 25 ), and chemokine receptors on Tregs are involved in the recruitment of these cells to sites of persistent inflammation ( 26 , 27 ). Recent study indicated that CCR4 and CXCR3 may participate in psoriasis recurrence or redistribution to distant sites ( 28 ). Therefore, we proposed that the accumulation of orbit-infiltrating Tregs in IOI may be due to the elevated expression of CCR4/CCR6 in circulating Tregs and increased levels of the corresponding ligand CCL17 in tissues, which might induce the homing of circulating Tregs into the orbit in patients with IOI.…”
Section: Discussionmentioning
confidence: 99%
“…Chemokine-induced trafficking and recruitment of leukocytes is involved in the inflammatory response ( 25 ), and chemokine receptors on Tregs are involved in the recruitment of these cells to sites of persistent inflammation ( 26 , 27 ). Recent study indicated that CCR4 and CXCR3 may participate in psoriasis recurrence or redistribution to distant sites ( 28 ). Therefore, we proposed that the accumulation of orbit-infiltrating Tregs in IOI may be due to the elevated expression of CCR4/CCR6 in circulating Tregs and increased levels of the corresponding ligand CCL17 in tissues, which might induce the homing of circulating Tregs into the orbit in patients with IOI.…”
Section: Discussionmentioning
confidence: 99%
“…Memory T cells are also somewhat resistant to immunosuppression 48 or immunoregulation 49 . Few studies have demonstrated that CD4 + T CM cells are significantly increased in patients with psoriasis 10 while circulating CLA + CCR4 + CD8 + T CM cells are also expanded in the patients 11 , indicating that T CM cells may be involved in the pathogenesis of psoriasis. On the other hand, T RM cells never recirculate through the blood once they reside in the skin.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have highlighted an important role for memory T cells in the pathogenesis and manifestation of psoriasis, especially its recurrence 7 - 9 . It has been shown that either CD4 + or CD8 + central memory T (T CM ) cells are increased in circulating peripheral blood of psoriasis patients 10 , 11 . T CM cells can also expand upon re-challenging in vitro and develop into Th17 cells 12 .…”
Section: Introductionmentioning
confidence: 99%
“…To automatically assess fluorescence compensation, MACS Comp Bead Kits (Miltenyi Biotec) as well as the antibodies used in the assay were utilized. In order to evaluate T ang and very rare cells (EPCs) in peripheral blood we used Fluorescence Minus One (FMO) control procedure to evaluate non-specific fluorescence when defining positive events as previously described (28), since it does not contain the antibody in the detector of interest representing the best control for any given marker of interest in a multicolor staining combination. Representative FMO for the analysis of very rare EPC subpopulation is shown in Supplemental Figure 1.…”
Section: Flow Cytometric Analysismentioning
confidence: 99%